Pengetahuan Bahaya Narkoba di Sekolah Menengah Kejuruan Wirakarya II Ciparay Tahun 2021 - Deni Arisandi (Lembaga Pengembangan Kinerja Dosen, 2021)
Adolescence is a transition period, namely a phase of development between childhood and adulthood. The main problem for teenagers in general is the search for identity. They experience an identity crisis. This is a problem for every teenager. implementation of activities to deliver material on the dangers of drugs. The activities were carried out together by the students as planned. The participants' ability to answer material questions can be said to be good (75%) correctly. Delivery of material using lecture and demonstration methods supports participants' ability to master the material presented by the service team. Education about the dangers of drugs is going well. Increased knowledge and skills for participants